Consumers’ Valuation of Academic and Equality-inducing Aspects of School Performance in England - Andreou, Sofia N.; Pashardes, Panos (My University, 2013)
This paper investigates the willingness of households to pay for academic and equality-inducing (deprivation-compensating) components of the Contextual Value Added (CVA) indicator of school quality used in England. Semi-parametric and parametric analysis shows that consumers are willing to pay for houses in the catchment area of primary and secondary schools with high academic achievement, as measured by the mean score; whereas, the component of the CVA indicating equality-inducing aspects of school performance is found to have a positive effect only on the price of houses in the catchment area of primary schools in London; its impact on the price of houses elsewhere is mostly negative. The role played by the CVA as a guide to choosing a school and the implications which our results can have for school funding are considered.
Keywords: Consumer Valuation; Education Equality; School Performance; Hedonic Analysis; Contextual Value Added